Incidence of tuberculosis in the state of Sergipe between 2017 and 2022: An epidemiological study (Research, Society and Development, 2023)
To evaluate the epidemiological profile of Tuberculosis cases in Sergipe between 2017 and 2022. This is an epidemiological study carried out using data made available by the Department of Informatics of the Unified Health System (DATASUS) through information collected through Notifiable Diseases Information System (SINAN). The collected data were stored and tabulated in Microsoft Office Excel®, so that it was possible to perform absolute and relative frequency. There were 5,730 cases of TB in the analyzed period in Sergipe, most cases (n = 3,726) were laboratory diagnosed, with the highest prevalence being in males (73.6%) and in young adults (60.73%). Pulmonary TB was responsible for 88% of the cases, while the most common sites of extrapulmonary TB (10.4%) were the pleural and lymph node. Some risk factors were observed in individuals with TB in Sergipe, such smoking, use of illicit substances and HIV infection. It is noteworthy that only 26.6% of the cases underwent directly observed treatment. There was a reduction in cases detected during the pandemic period. The profile of TB in Sergipe was marked by young male adults, with risk factors such as HIV infection and smoking being found. An important limitation of this study was the fact that there was a significant percentage of variables filled in as ignored/blank.